The Relationship between Sleep Quality, Coffee Drinking Habits, Drug Use and the Incidence of Dyspepsia at the South City Health Center - Najwa Miranti I Lashari; Sirajuddien Bialangi; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Dyspepsia is a disorder of the upper gastrointestinal tract that is still a global and national health problem. Globally, the prevalence of dyspepsia is estimated to reach 40–50% of the population. In Indonesia, dyspepsia is among the top 10 most common diseases in health care facilities with a fairly high number of cases and continues to increase every year. In Gorontalo Province, the number of dyspepsia cases in 2024 will be recorded at 6,812 cases. Meanwhile, at the South City Health Center, there will be 587 cases in 2025. In the work area of the South City Health Center, dyspepsia is still a health problem that needs attention. The incidence of this disease is influenced by various risk factors, such as sleep quality, coffee drinking habits, and drug use. This study aims to analyze the relationship between these factors and the incidence of dyspepsia. This study uses a quantitative method with a Cross-sectional design. The research sample amounted to 73 respondents who were selected using the Accidental sampling technique on patients of productive age (15–59 years) at the South City Health Center. Data was collected using a questionnaire and analyzed with the Chi-Square statistical test to find out the relationship between variables. The results showed that there was a significant relationship between sleep quality (p=0.001), coffee drinking habits (p=0.011), and drug use (p=0.023) with the incidence of dyspepsia. There is a relationship between sleep quality, coffee drinking habits, and drug use with the incidence of dyspepsia at the South City Health Center. Improving sleep quality, limiting coffee consumption, and rational use of drugs are needed as an effort to prevent dyspepsia.